Fabrication and characterization of targeting liposomes for nanomedicine applications - Yeo, Edmund Wei Liang (2018)
Atherosclerosis is one of the leading causes of coronary heart disease in the developed world. While there are conventional oral medications for atherosclerosis, oral drug delivery systems are inefficient with issues of low bioavailability, gastro intestinal side effects and liver toxicity. As such active targeting drug delivery systems (DDS) such as liposome-targeting peptide conjugates have been identified as a potential candidate in atherosclerosis drug delivery that is able to overcome the limitations of conventional DDS. This study aims to fabricate different composition of liposomes via the “high pressure filter extrusion” technique, fabricated liposomes are then subsequently conjugated with targeting peptides to liposomal surface. Characterisation of size and stability of all liposomes will be performed via Dynamic Light scattering (DLS). Liposome fabricated by via “High pressure filter extrusion” technique using an 80nm Polycarbonate filter membrane are found to undergo expansion of 31%-51% and fall within the acceptable range of 100-200nm in size. Zeta potential stability of fabricated liposome are dependent on phospholipids composition. Conjugation of targeting peptide to liposome was first performed using EDC, Sulfo-NHS activation methodology. Conjugated DPPC-COOH-Peptide 1 liposome with a size of 152.7nm, stable zeta potential of -37.7mV and conjugation efficiency of 70.2% (HPLC analysis) was identified as the lead candidate for atherosclerosis drug delivery. While other conjugation methodology involving the spontaneous formation of thio-maleimide was explored in this study, conjugation efficiency was limited due to the oxidation of sulfhydryl (-SH) groups on targeting peptide 2, which resulted in internal formation of cystine complexes. Conjugation efficiency was found to be a maximum of 32.22% via HPLC analysis of aforementioned strategy involving thio-Maleimide bond formation. To better enhance HPLC analysis results, dialysis of conjugated liposome-targeting peptide was performed in 1:3 (Acetonitrile/ DI water) by volume. HPLC results showed a 90% dialysis efficiency under 1:3 (Acetonitrile/DI water) medium. This is a 75% increase in efficiency from dialysis under 100% DI water which only recorded a dialysis efficiency of 15%.